2005
DOI: 10.1111/j.1365-2362.2005.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐A, VEGF‐D and VEGF‐DΔNΔC induced intimal hyperplasia in carotid arteries

Abstract: Adventitial delivery of adenoviruses encoding VEGF-A, VEGF-D and VEGF-D(DeltaNDeltaC) increased intimal hyperplasia in the rabbit collar model. Adventitial angiogenesis correlated positively with the intimal hyperplasia. These results indicated that efficient adventitial production of VEGF-A, VEGF-D and VEGF-D(DeltaNDeltaC) can cause thickening of the inner layer of the artery in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 23 publications
1
68
0
Order By: Relevance
“…This is in line with the suggestion that adventitial angiogenesis contributes to atherosclerotic plaque growth because the degree of adventitial angiogenesis correlates with the extend of neointima formation. 21,22 In addition, stimulation of adventitial angiogenesis, by administration of endothelial progenitor cells or adventitial application of VEGF, results in increased neointima formation. 23,24 Recently, circulating hematopoietic stem cells were shown to differentiate into vascular cells that participate in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the suggestion that adventitial angiogenesis contributes to atherosclerotic plaque growth because the degree of adventitial angiogenesis correlates with the extend of neointima formation. 21,22 In addition, stimulation of adventitial angiogenesis, by administration of endothelial progenitor cells or adventitial application of VEGF, results in increased neointima formation. 23,24 Recently, circulating hematopoietic stem cells were shown to differentiate into vascular cells that participate in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, local gene transfer of VEGF-A significantly increases intimal hyperplasia after balloon injury 49 or application of silastic collars. 52 Intraluminal infusion of VEGF-A to denuded rat carotid arteries doubled the mitogenic response to infused FGF-2 by increasing intimal SMC replication. 24 Moreover, systemic delivery of soluble Flt1 (which blocks VEGF-A-VEGFR1/Flt1 binding) attenuated neointima formation after balloon injury without affecting luminal reendothelialization.…”
Section: Malabanan Et Al Atf-4 Controls Vegf-a and Neointima Formationmentioning
confidence: 99%
“…33 Similarly, adenoviral gene transfer of VEGF-A and VEGF-D to adventitia induced robust adventitial angiogenesis, whereas VEGF-B adenoviral gene transfer failed to do so. 34,45 Another study also showed that VEGF-B 167 gene delivery to the skin or ischemic limb did not induce blood vessel growth. 10 Furthermore, VEGF-B 167 recombinant protein injection into mouse eyes at a dose effective for retinal neuron survival did not induce ocular angiogenesis.…”
Section: Introductionmentioning
confidence: 99%